2011 37th EUROMICRO Conference on Software Engineering and Advanced Applications 2011
DOI: 10.1109/seaa.2011.76
|View full text |Cite
|
Sign up to set email alerts
|

A Study of the Characteristics of Behaviour Driven Development

Abstract: Abstract-Behaviour Driven Development (BDD) has gained increasing attention as an agile development approach in recent years. However, characteristics that constituite the BDD approach are not clearly defined. In this paper, we present a set of main BDD charactersitics identified through an analysis of relevant literature and current BDD toolkits. Our study can provide a basis for understanding BDD, as well as for extending the exisiting BDD toolkits or developing new ones.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
59
0
3

Year Published

2013
2013
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 107 publications
(62 citation statements)
references
References 5 publications
0
59
0
3
Order By: Relevance
“…The Behavior Driven Development [52] software approach puts a strong focus on explicitly stating the behavior of system components. In particular, Behavior Driven Development focuses on understanding the behavior of the components defined as simple given-when-then scenarios.…”
Section: Related Workmentioning
confidence: 99%
“…The Behavior Driven Development [52] software approach puts a strong focus on explicitly stating the behavior of system components. In particular, Behavior Driven Development focuses on understanding the behavior of the components defined as simple given-when-then scenarios.…”
Section: Related Workmentioning
confidence: 99%
“…This is further enhanced by including terms from the business domain in the domain-specific language. Solis and Wang (2011) reviewed the available literature and a number of tools for behaviour-driven development in 2011. They found that the area was still under development and that the domain-specific languages supported by the tools limited the requirements expressiveness.…”
Section: The Agile Approach Of Integrating Requirements Engineering Wmentioning
confidence: 99%
“…what a system should do, specified so that both the developers and the domain experts would understand. BDD enables users to describe the required system behaviour as executable user stories and the acceptance criteria as executable scenarios attached to these [77,78]. The user stories should have a clear and explicit title, a short introductory narrative section that specifies Who (As a), Which (I want) and What (So that) and acceptance criteria or scenarios which would describe each specific case of the narrative [76].…”
Section: Assessing Performance With Behaviour Driven Developmentmentioning
confidence: 99%